Spatiotemporal gait changes in healthy pregnant women and women with pelvic girdle pain: a systematic review - Wong,JKL; McGregor,AH (Journal of Back and Musculoskeletal Rehabilitation, 2018)
INTRODUCTION: Gait is affected in women with pelvic girdle pain (PGP), a musculoskeletal condition affecting 20% of pregnant women. Whilst there is evidence of spatiotemporal changes in gait during healthy pregnancy, less is known in relation to women with PGP. Appreciating gait characteristics during healthy pregnancy could inform our understanding of the role of gait in PGP. PURPOSE: The purpose of this review was to systematically analyse differences in the spatiotemporal parameters of gait in healthy pregnant women and those with PGP, and to make recommendations to improve research methods in investigating gait in PGP women. METHODS: The review was undertaken following the PRISMA guidelines. Three databases and pre-existing literature were electronically and manually searched. Study selection and data extraction were conducted by two reviewers. Quality assessment was performed using the NHLBI tool for Observational Cohort and Cross-sectional Studies. RESULTS: The search returned 2925 results. Fourteen studies were selected for data extraction. Twelve studies investigated gait in healthy pregnant women and two in PGP women. Studies employed either a cohort or cross-sectional design and used various methods to assess gait. Three, nine and two studies were high, medium and low in quality, respectively. Direct comparisons between studies were impeded due to incomparable gestational time-points investigated, in addition to variations in gait parameters and definitions used. CONCLUSION: Evidence from studies on healthy pregnant women could inform future research on PGP women, for which current evidence is scarce. We recommend the standardisation of critical factors to allow inter-study comparisons for a meta-analysis.